Public-private Partnership in the Governance of Koa-Koa Beach Tourism, Pasangkayu Regency - Ikmal, ‎; Ibrahim, Muh Akmal (KnE Social Sciences, 2025)
This study investigates the role of public-private partnerships (PPPs) in enhancing tourism governance at Koa-Koa beach, located in the peripheral region of Pasangkayu Regency, West Sulawesi. Despite its ecological and cultural richness, the area faces developmental stagnation due to inadequate infrastructure, fragmented institutional coordination, and limited engagement from both private sectors and local communities. Employing a qualitative-descriptive methodology, data were collected through semi-structured interviews with 18 stakeholders, field observations, and document analysis. Key challenges identified include regulatory ambiguities, overlapping institutional responsibilities, insufficient stakeholder incentives, and low institutional capacity. Drawing lessons from successful PPP implementations in Malaysia and the Philippines, this study proposes a context-sensitive governance framework centered on transparency, shared accountability, equitable risk distribution, and inclusive participation. Findings demonstrate that well-structured PPPs can bridge infrastructure and funding gaps, promote sustainable tourism, safeguard environmental and cultural assets, and stimulate inclusive economic growth. Recommendations emphasize the need to build institutional trust, establish operational guidelines, and enhance legal clarity to facilitate PPP implementation in underdeveloped regions.